Foreign capital inflows and economic growth in Kenya - Ojiambo, Elphas; Ocharo, Kennedy N. (My University, 2016)
Foreign Aid, Foreign Direct Investment and Remittances remain important and stable source of foreign capital inflows to developing countries, as they bring in large amounts of foreign currency that help sustain the balance of payments. Studies have for years examined the nexus between aid and growth, FDI and growth and to a limited extent remittances and growth. While the focus has largely been on the first two nexuses, there is an increasing literature on the remittance-growth nexus. There have however been very few studies that have sought to consider the combined impact of each of these variables on economic growth. This paper examined the above issue within a country-specific focus (Kenya) using Granger Causality and Autoregressive Distributed Lag procedures. We found that there is uni-directional causality between economic growth and Foreign Direct Investment, Labour and Foreign Aid and Macroeconomic Policy environment and Foreign Direct Investment. The study found that Aid has a positive and significant effect on economic growth when the macroeconomic policy environment is accounted for. Remittances are found to have a short-run negative effect on economic growth but positive effect after a period of one year. We also found a negative relationship between Foreign Direct Investment and economic growth in Kenya possibly due to its volatility and its low level of inflow.
Keywords: Foreign Aid; Remittances; FDI; Macroeconomic Policy; Economic Growth